Tunable beam-type piezoelectric energy harvester using a geared-motor-driven system - Hossain, MD Mofazzal; Mohd Firdaus, Hassan; Muhammad Hatifi, Mansor; Abbas, Nazir; Atallah, Kamel Eddine; Al Amin, Mohamed Sultan; Fudhail, Abdul Munir (SAGE Publications, 2026)
Due to drawbacks such as bulkiness in slider-mass systems and nonlinear effects in magnetic-tuning systems, a geared-motor-driven system is seen as a solution to overcome these issues in vibration energy harvesters. This paper presents a novel tunable energy harvester using a geared-motor-driven system, where the natural frequency of a beam-type piezoelectric energy harvester is adjusted to match the excitation frequency. The design details and operational mechanism are comprehensively described. The relationship between the beam length and its natural frequencies is determined using finite element analysis (FEA), yielding a third-degree polynomial equation that is integrated into the software-based control system. Experimental results demonstrate the system’s capability for two-way tuning, effectively both shortening and lengthening the beam to track resonance. The process also identified an optimal load resistance of approximately 4–8 kV for maximum power transfer. The results show that the power enhancement ratio exceeds 10 in optimal cases, and the voltage enhancement ratio reaches up to 6.3 when the beam’s natural frequency is aligned with the excitation frequency. Furthermore, the study reveals that shorter, stiffer beams generate significantly higher power at resonance due to a greater strain gradient. While the absolute power values are in the nanowatt range, the system successfully validates the proposed tuning mechanism, demonstrating a substantial enhancement in harvesting efficiency.